Manajemen Risiko sebagai Mediator dalam Keterkaitan Inklusi Keuangan dan Kinerja UKM Balikpapan - Gusmawati; Ribka Patta; Agus Rahayu; Hery Eko Prastiyo; Nurlia Nurlia (Lembaga Teewan Journal Solutions, 2026)
This study aims to examine the role of risk management as a mediating variable in the relationship between financial inclusion and SME performance. The study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart-PLS version 4. Data were collected through questionnaires distributed to 150 SME owners and managers in Balikpapan, Indonesia, selected using purposive sampling. The findings reveal that financial inclusion does not have a significant direct effect on SME performance. However, financial inclusion has a positive and significant effect on risk management, while risk management significantly improves SME performance. Furthermore, the study confirms that risk management significantly mediates the relationship between financial inclusion and SME performance. These findings indicate that access to formal financial services alone is insufficient to improve SME performance unless supported by effective risk management practices. The study contributes to the literature by highlighting the strategic role of risk management as an important mechanism through which financial inclusion can enhance business performance. Practically, the findings suggest that policymakers and financial institutions should complement financial inclusion programs with risk management training and managerial assistance for SMEs to ensure sustainable business growth and resilience.